Gas-electricity coupled gelatin and sodium alginate composite hydrogel as well as preparation method and application thereof

Through gas-electric coupling of gelatin and sodium alginate composite hydrogel, loaded with sodium hydrosulfide and conductive microfiber, the lack of bidirectional regulatory function and drug administration methods in the treatment of periodontitis is solved, and sustained release is achieved The anti-inflammatory and immune regulation effects of hydrogen sulfide significantly improve the repair effect of periodontitis.

CN119235751APending Publication Date: 2025-01-03WEST CHINA HOSPITAL SICHUAN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410930365.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-11
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing periodontitis treatment biological materials cannot have two-way regulatory functions, which limits their practical application in periodontitis repair, and there are side effects and rapid drug efficacy loss.

Method used

Develop a gas-electrically coupled gelatin and sodium alginate composite hydrogel, coupled with 3,4-ethylenedioxythipyridine-modified silk-coupled bovine serum albumin nanoparticles and polyphenols Microfibers, combined with polyethylene glycol diglycidyl ether, prepare hydrogels with conductive and sustained release hydrogen sulfide functions for targeted regulation of the pathological microenvironment.

Benefits of technology

The hydrogel can slowly release hydrogen sulfide, promote blood vessel and bone formation, has anti-inflammatory and immune regulation effects, improves the repair effect of periodontitis, and is good biocompatible because the materials used are non-toxic.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119235751A_ABST
    Figure CN119235751A_ABST
Patent Text Reader

Abstract

The invention provides gas-electricity coupled gelatin and sodium alginate composite hydrogel as well as a preparation method and application thereof, and belongs to the technical field of biological materials. The gas-electricity coupled gelatin and sodium alginate composite hydrogel disclosed by the invention is prepared from the following raw materials in parts by weight: 1 to 10 parts of gelatin, 1 to 10 parts of sodium alginate, 0.1 to 1 part of polyphenol modified fibroin microfiber coupled with 3, 4-ethylenedioxythiophene, 0.05 to 0.5 part of sodium hydrosulfide loaded bovine serum albumin nanoparticles, 1 to 10 parts of polyethylene glycol diglycidyl ether and 100 to 200 parts of water. The hydrogel has good biocompatibility and mechanical properties, is good in stability, can slowly release hydrogen sulfide gas, has relatively good conductivity, has anti-inflammatory and immunoregulation effects, can attract stem cells and promote angiogenesis and bone formation, has an excellent repair effect on diabetic periodontitis, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomaterials, and in particular relates to a gas-electrically coupled gelatin and sodium alginate composite hydrogel and a preparation method and application thereof. Background Art

[0002] As a complex supporting tissue of teeth, periodontal tissue plays multiple functions of nutrition, fixation and transmission of chewing force. Periodontitis is a chronic inflammatory disease induced by periodontal pathogens, which may cause irreversible damage to periodontal tissues, eventually leading to loose and falling teeth, and is closely related to human quality of life and medical burden. According to the latest research, the incidence of periodontitis in adults in my country is as high as 80%. At the same time, periodontitis and diabetes have a two-way relationship. On the one hand, diabetes is one of the established risk factors for periodontitis, which leads to a 3-5-fold increase in incidence and accelerated periodontal destruction; on the other hand, periodontitis is a triggering factor of diabetes, which has an adverse effect on blood sugar control and leads to the occurrence of diabetic complications such as cardiopulmonary dysfunction. Therefore, the treatment of periodontal tissue damage caused by periodontitis remains an important issue facing the world.

[0003] In recent years, the disease microenvironment has received attention as a regulatory target in biomedical treatment. The microenvironment of chronic inflammatory diseases such as periodontitis is characterized by the accumulation of a large amount of reactive oxygen species (ROS), aggravated inflammatory response, and dysregulation of macrophage polarization. This pathological microenvironment induces aging and reduced differentiation potential of functional cells such as mesenchymal stem cells (MSCs), which is not conducive to tissue repair and regeneration. The transition from an aggravated inflammatory microenvironment to a regenerative microenvironment is the key to promoting tissue regeneration in biomedicine.

[0004] However, most of the biomaterials currently used for tissue regeneration focus on either osteogenic differentiation of MSCs or inhibition of the periodontal inflammatory microenvironment, and do not yet have a two-way regulatory function, which limits their practical application in periodontitis repair. In addition, oral systemic administration of drugs for the treatment of periodontitis has significant side effects, while local administration has the disadvantages of insufficient drug concentration and rapid loss of efficacy. Therefore, it is of great significance to develop periodontitis repair products that can load and release drugs and target the pathological microenvironment. Summary of the invention

[0005] The purpose of the present invention is to provide a gas-electrically coupled gelatin and sodium alginate composite hydrogel and a preparation method and application thereof.

[0006] The present invention provides a gas-electrically coupled gelatin and sodium alginate composite hydrogel, which is prepared from the following raw materials in weight ratio:

[0007] 1-10 parts of gelatin, 1-10 parts of sodium alginate, 0.1-1 parts of polyphenol-modified silk microfibers coupled with 3,4-ethylenedioxythiophene, 0.05-0.5 parts of bovine serum albumin nanoparticles loaded with sodium hydrosulfide, 1-10 parts of polyethylene glycol diglycidyl ether, and 100-200 parts of water.

[0008] Furthermore, the aforementioned gas-electrically coupled gelatin and sodium alginate composite hydrogel is prepared from raw materials in the following weight ratio:

[0009] 8 parts of gelatin, 2 parts of sodium alginate, 0.2 parts of polyphenol-modified silk microfibers coupled with 3,4-ethylenedioxythiophene, 0.1 parts of bovine serum albumin nanoparticles loaded with sodium hydrosulfide, 6.84 parts of polyethylene glycol diglycidyl ether, and 100 parts of water.

[0010] Furthermore, the polyphenol-modified 3,4-ethylenedioxythiophene-coupled silk microfibers are prepared from polydopamine-modified silk microfibers, 3,4-ethylenedioxythiophene and ferric chloride hexahydrate as raw materials;

[0011] The mass volume ratio of the polydopamine-modified silk microfibers and 3,4-ethylenedioxythiophene is 1 g: 1-10 mL; the mass ratio of the polydopamine-modified silk microfibers and ferric chloride hexahydrate is 1:20-30;

[0012] Preferably, the mass volume ratio of the polydopamine-modified silk microfibers to 3,4-ethylenedioxythiophene is 1 g:4 mL; the mass ratio of the polydopamine-modified silk microfibers to ferric chloride hexahydrate is 1:20.

[0013] Furthermore, the method for preparing the polyphenol-modified 3,4-ethylenedioxythiophene-coupled silk microfibers comprises the following steps:

[0014] 1) dispersing polydopamine-modified silk microfibers, 3,4-ethylenedioxythiophene and ferric chloride hexahydrate in a solvent, stirring evenly and then standing;

[0015] 2) After centrifugation, retain the silk fiber precipitate in the lower layer, wash it with water, and freeze-dry it to obtain the silk fiber precipitate;

[0016] Preferably,

[0017] In step 1), the solvent is an ethanol aqueous solution, and the volume ratio of ethanol to water in the ethanol aqueous solution is 3:1;

[0018] And / or, in step 1), the standing time is 1 to 5 hours.

[0019] Furthermore, the method for preparing the polydopamine-modified silk microfibers comprises the following steps:

[0020] (a) placing degummed silk into a solution containing dopamine and stirring;

[0021] (b) after stirring in step (a), half of the solution is replaced with water, and then allowed to stand;

[0022] (c) adding sodium hydroxide to the solution after standing in step (b), heating for reaction, and then ultrasonic treatment;

[0023] (d) centrifuging the solution after treatment in step (c), washing the precipitate with water, and freeze-drying to obtain the product.

[0024] Further,

[0025] In step (a), the mass ratio of the degummed silk fibroin to dopamine is 6:(13-14);

[0026] And / or, in step (a), the solvent of the dopamine-containing solution is tris-HCl buffer;

[0027] And / or, in step (a), the stirring time is 10 to 20 hours;

[0028] And / or, in step (b), the standing time is 10 to 20 hours;

[0029] And / or, in step (c), the mass ratio of the sodium hydroxide to the degummed silk fibroin in step (a) is (0.7-1):1;

[0030] And / or, in step (c), the heating reaction temperature is 70-90° C. and the time is 1-5 h;

[0031] And / or, in step (c), the ultrasonic treatment time is 1 to 5 hours;

[0032] Preferably,

[0033] In step (a), the preparation method of degummed silk fibroin comprises the following steps: placing silk in an alkaline solution with a pH of 9 to 10 and boiling it, then cooling it to room temperature, stirring it, and drying it to obtain the degummed silk fibroin.

[0034] Furthermore, the method for preparing the sodium hydrosulfide-loaded bovine serum albumin nanoparticles comprises the following steps:

[0035] (A) dissolving bovine serum albumin in water to obtain a bovine serum albumin solution;

[0036] (B) dissolving sodium hydrosulfide in anhydrous ethanol to obtain a sodium hydrosulfide ethanol solution;

[0037] (C) adding sodium hydrosulfide ethanol solution to bovine serum albumin solution, and then adding N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride to react;

[0038] (D) centrifuging after the reaction, collecting the precipitate, and drying the precipitate to obtain;

[0039] The mass ratio of the bovine serum albumin to sodium hydrosulfide is 1:(0.01-0.05).

[0040] Further,

[0041] In step (A), the concentration of the bovine serum albumin solution is 1 to 5 wt %;

[0042] And / or, in step (B), the concentration of the sodium hydrosulfide ethanol solution is 0.1-0.5wt%;

[0043] And / or, in step (C), the rate of adding the sodium hydrosulfide ethanol solution to the bovine serum albumin solution is 0.1 to 1 mL / min;

[0044] And / or, in step (C), the mass ratio of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride to bovine serum albumin is (0.01-0.05):1;

[0045] And / or, in step (C), the reaction temperature is 20-30°C and the reaction time is 10-20h;

[0046] Preferably,

[0047] In step (A), the concentration of the bovine serum albumin solution is 2 wt %;

[0048] And / or, in step (B), the concentration of the sodium hydrosulfide ethanol solution is 0.1wt%;

[0049] And / or, in step (C), the rate of adding the sodium hydrosulfide ethanol solution into the bovine serum albumin solution is 0.5 mL / min.

[0050] The present invention also provides a method for preparing the aforementioned gas-electrically coupled gelatin and sodium alginate composite hydrogel, which comprises the following steps:

[0051] (1) Dissolve gelatin and sodium alginate in water;

[0052] (2) adding polyphenol-modified 3,4-ethylenedioxythiophene-coupled silk microfibers, sodium hydrosulfide-loaded bovine serum albumin nanoparticles, and polyethylene glycol diglycidyl ether to the solution in step (1) for cross-linking;

[0053] (3) After crosslinking in step (2), the obtained hydrogel is immersed in a Ca-containing 2+ Further cross-linking in an aqueous solution of ions to obtain;

[0054] Preferably,

[0055] In step (2), the cross-linking time is 20 to 30 hours;

[0056] And / or, in step (3), the cross-linking time is 1 to 5 hours.

[0057] The present invention also provides the use of the aforementioned gas-electrically coupled gelatin and sodium alginate composite hydrogel in the preparation of a drug for treating periodontitis;

[0058] Preferably, the periodontitis is diabetic periodontitis.

[0059] The present invention prepares a hydrogel with good conductivity by introducing PEDOT-PSF with good conductivity and dispersibility into the hydrogel, and utilizes the endogenous electric field generated by tissue defects to promote orderly arrangement of cells, increase calcium ion influx, and synergistically promote osteogenic differentiation.

[0060] As a gas signal molecule, hydrogen sulfide can play a good role in promoting angiogenesis and osteogenesis at low concentrations, and has certain toxicity to tissues and cells at high concentrations. However, its commonly used donor sodium hydrosulfide reacts violently with water and quickly releases a large amount of hydrogen sulfide gas molecules. The development of a drug loading system that can encapsulate sodium hydrosulfide and slowly release hydrogen sulfide is of great significance for the application of hydrogen sulfide in various diseases. The sodium hydrosulfide of the present invention is encapsulated in micro-nano particles, which have good stability, isolate water, better maintain the activity of molecules, and avoid sodium hydrosulfide from losing activity when reacting with water during the preparation process. Micro-nano particles degrade slowly, making the hydrogen sulfide action time longer and the tissue induction effect better. Different growth factors can also be encapsulated in nanoparticles to achieve the synergistic and controlled release of multiple growth factors. A more optimized drug loading and sustained release method for hydrogen sulfide is performed to obtain a gelatin and sodium alginate composite hydrogel that can load and slowly release hydrogen sulfide and give it the performance of multi-directional regulation of the disease microenvironment, which is of great significance in the field of periodontitis treatment.

[0061] Compared with the prior art, the present invention has the following beneficial effects:

[0062] (1) Loading and slow release of hydrogen sulfide. The sodium hydrosulfide-loaded bovine serum albumin nanoparticles prepared by the present invention can be loaded with sodium hydrosulfide and can slowly release hydrogen sulfide for a long time.

[0063] (2) Promote angiogenesis. The bovine serum albumin nanoparticles loaded with sodium hydrosulfide prepared by the present invention slowly release hydrogen sulfide, which can promote the differentiation of stem cells into angiogenesis.

[0064] (3) Promote bone formation. The bovine serum albumin nanoparticles loaded with sodium hydrosulfide prepared by the present invention slowly release hydrogen sulfide, which can recruit stem cells and promote the osteogenic differentiation of stem cells.

[0065] (4) PEDOT-PSF has good electrical conductivity and has the characteristics of promoting orderly cell arrangement, increasing calcium ion influx, and synergistically promoting osteogenic differentiation.

[0066] (5) Anti-inflammatory. The PEDOT-PSF prepared by the present invention utilizes the catechol group of polyphenol as an adhesion site, retains its ability to eliminate free radicals and has good anti-inflammatory properties.

[0067] (6) Immunomodulatory function. The synergistic effect of PEDOT-PSF conductivity and hydrogen sulfide has an immunomodulatory effect, reducing M1 macrophages and promoting the differentiation of M2 macrophages.

[0068] (7) Mechanical properties: The silk fibroin and gelatin composite scaffold prepared by the present invention has good mechanical properties and is suitable for periodontal tissue repair.

[0069] (8) The reagents used in the preparation process of the present invention, such as polyphenols, bovine serum albumin, 3,4-ethylenedioxythiophene, polyethylene glycol diglycidyl ether, etc., are all non-toxic, and the prepared gelatin and sodium alginate composite hydrogel has good biocompatibility.

[0070] (9) Gas-electricity synergistic effect is superior to the function of single component.

[0071] In summary, the present invention provides a gas-electrically coupled gelatin and sodium alginate composite hydrogel, which has good biocompatibility and mechanical properties, good stability, can slowly release hydrogen sulfide gas, and has good conductivity, plays an anti-inflammatory and immunomodulatory role, and can also attract stem cells, promote angiogenesis and bone formation, has excellent repair effects on diabetic periodontitis, and has good application prospects.

[0072] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.

[0073] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Figure 1The figures are scanning electron microscope images of bovine serum albumin nanoparticles loaded with sodium hydrosulfide (NaHS@BNP) of the present invention and the hydrogen sulfide release of the gas-electric coupled gelatin and sodium alginate composite hydrogel (BNP-PEDOT-PSF-AG): a is a scanning electron microscope image of NaHS@BNP; b is the hydrogen sulfide release of BNP-PEDOT-PSF-AG hydrogel.

[0075] Figure 2 The scanning electron microscope images and mechanical property test results of the gas-electric coupled gelatin and sodium alginate composite hydrogel (BNP-PEDOT-PSF-AG) of the present invention are as follows: a is a scanning electron microscope image of BNP-PEDOT-PSF-AG hydrogel, and the arrows are PEDOT-PSF and NaHS@BNP; b is the compression property test results of different hydrogels, *P<0.05 compared with the AG group; c is the tensile property test results of different hydrogels, *P<0.05 compared with the AG group; d is the cyclic compression test result of BNP-PEDOT-PSF-AG hydrogel; e is the degradation test result of different hydrogels.

[0076] Figure 3 The conductive properties of the gas-electrically coupled gelatin and sodium alginate composite hydrogel (BNP-PEDOT-PSF-AG) of the present invention are as follows: a is the light-emitting diode lighting up in the BNP-PEDOT-PSF-AG hydrogel connection circuit prepared in Example 1; b is the conductivity of the BNP-PEDOT-PSF-AG hydrogel prepared with different PEDOT-PSF contents; c is the stable light emission of the light-emitting diode in the BNP-PEDOT-PSF-AG hydrogel compression recovery connection circuit prepared in Example 1; d is the conductivity of the BNP-PEDOT-PSF-AG hydrogel prepared in Example 1 under different compression amounts.

[0077] Figure 4 The figures show the arrangement of human periodontal ligament stem cells on the gas-electrically coupled gelatin and sodium alginate composite hydrogel (BNP-PEDOT-PSF-AG) of the present invention and the influx of calcium ions under a high-sugar inflammatory environment: a shows the arrangement and extension of periodontal ligament stem cells on hydrogels at different voltages; b shows the statistics of the extension of periodontal ligament stem cells on hydrogels at different voltages; c shows the KEGG analysis of periodontal ligament cell sequencing on gas-electrically coupled gelatin and sodium alginate composite hydrogel (BNP-PEDOT-PSF-AG) and control hydrogel (PSF-AG); d shows the heat map of related gene expression of three groups of BNP-PEDOT-PSF-AG, PEDOT-PSF-AG and PSF-AG; e shows the osteogenic mechanism of gas-electrically coupled gelatin and sodium alginate composite hydrogel.

[0078] Figure 5Figure 2 shows the regulatory effects of different hydrogels on macrophage polarization direction and the production of pro-inflammatory / anti-inflammatory factors: a is the relative gene expression of M1 macrophage-related genes interleukin 1β (IL-1β), tumor necrosis factor α (TNF-α), and inducible nitric oxide synthase (NOS2) detected by RT-qPCR on different hydrogels; b is the relative gene expression of M2 macrophage-related genes arginase 1 (Arg-1), interleukin 10 (IL-10), and DECTIN detected by RT-qPCR on different hydrogels; c is the gas-electric coupled gelatin and sodium alginate composite hydrogel d is the GSEA analysis of lipid metabolism by sequencing of THP-1 on the gel (BNP-PEDOT-PSF-AG) and the control hydrogel (AG); d is the GSEA analysis of glutathione peroxidase activity by sequencing of THP-1 on the gas-electrically coupled gelatin and sodium alginate composite hydrogel (BNP-PEDOT-PSF-AG) and the control hydrogel (AG); e is the heat map of the expression of related genes in the three groups of BNP-PEDOT-PSF-AG, PEDOT-PSF-AG, and AG; f is a diagram of the mechanism of macrophage polarization regulation by the gas-electrically coupled gelatin and sodium alginate composite hydrogel.

[0079] Figure 6 The results of the repairing effects of different hydrogels on local periodontal tissues of diabetic rats with periodontitis: a is a gross image; b is a CT three-dimensional reconstruction image; c is an X-ray image; d is a HE staining image.

[0080] Figure 7 These are the results of the local angiogenesis and osteogenesis promoting effects of different hydrogels on diabetic rats with periodontitis. DETAILED DESCRIPTION

[0081] The raw materials and equipment used in the specific embodiments of the present invention are all known products, which are synthesized by literature methods or obtained by purchasing commercially available products.

[0082] Example 1. Preparation of the gas-electric coupled gelatin and sodium alginate composite hydrogel of the present invention

[0083] 1. Preparation of polyphenol-modified 3,4-ethylenedioxythiophene-coupled silk microfibers (PEDOT-PSF):

[0084] Silk was boiled in a Na2CO3 aqueous solution (pH = 9) for 30 minutes and stirred at room temperature for 60 minutes to obtain degummed silk fibroin. 0.6g of dry degummed silk fibroin was placed in a dopamine (DA) tris-HCl buffer (dopamine concentration is 0.05M, 180mL, pH = 8) and stirred for 10 hours, and then half of the solution was replaced with double distilled water and allowed to stand for 12 hours. Subsequently, 0.42g NaOH was added to the solution, heated at 70°C for 3 hours, ultrasonically treated for 1 hour, resuspended with ultrapure water and centrifuged repeatedly 2-3 times, and freeze-dried to obtain polydopamine-modified silk fibroin microfibers (PSF).

[0085] Dried PSF (0.05 g), 3,4-ethylenedioxythiophene (EDOT, 200 μL) and FeCl3·6H2O (1 g) were dispersed in 50 mL of ethanol-water solution (volume ratio of ethanol to water was 3:1). After stirring evenly, the mixture was allowed to stand for 3 hours, and then centrifuged at 10000 g for 10 min using a high-speed centrifuge. The lower layer of silk fiber precipitation was retained, resuspended with ultrapure water, and centrifuged repeatedly 2-3 times, and freeze-dried to obtain polyphenol-modified silk fiber microfibers coupled with 3,4-ethylenedioxythiophene (PEDOT-PSF).

[0086] 2. Preparation of bovine serum albumin nanoparticles loaded with sodium hydrosulfide (NaHS-loaded BNP):

[0087] NaHS-loaded bovine serum albumin nanoparticles were prepared by desolvation method. 0.6 g bovine serum albumin (BSA) was added to 30 mL distilled water and dissolved to obtain a BSA solution. 0.03 g NaHS was dissolved in 30 mL anhydrous ethanol to form a NaHS / ethanol solution. Then, the NaHS / ethanol solution was added to the BSA solution at a rate of 0.5 mL / min to obtain a mixture. 18.75 mg N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC) was added to the mixture for BNP coupling. After stirring at room temperature for 12 h, the precipitate was collected by centrifugation (19760×g, 15 min, 4°C) and dried to obtain NaHS-loaded BNP (NaHS@BNP).

[0088] 3. Preparation of gas-electric coupled gelatin and sodium alginate composite hydrogel (BNP-PEDOT-PSF-AG hydrogel):

[0089] To synthesize BNP-PEDOT-PSF-AG hydrogel, 0.8 g of gelatin was dissolved in 10 ml of 2 wt.% sodium alginate aqueous solution. The solution was stirred at 65 °C for 1 h until the gelatin powder was completely dissolved. 0.02 g of PEDOT-PSF and 0.01 g of NaHS@BNP were added to the mixed solution, and 600 μL of polyethylene glycol diglycidyl ether (PEGDE) was added to the mixed solution to crosslink the gelatin. After crosslinking for 24 h, the hydrogel was immersed in 5% CaCl2 aqueous solution for 1 h to further crosslink the sodium alginate to obtain BNP-PEDOT-PSF-AG hydrogel.

[0090] For comparison, the present invention uses the same preparation method to prepare PEDOT-PSF-AG hydrogel, BNP-PSF-AG hydrogel, PSF-AG hydrogel and AG hydrogel. The raw material formulas of PEDOT-PSF-AG hydrogel, BNP-PSF-AG hydrogel, PSF-AG hydrogel and AG hydrogel are shown in Table 1.

[0091] Table 1. Raw material formula of hydrogels with different components

[0092]

[0093] The beneficial effects of the present invention are demonstrated below through specific test examples.

[0094] Experimental Example 1: Structural Characterization of Bovine Serum Albumin Nanoparticles Loaded with Sodium Hydrosulfide of the Present Invention

[0095] The morphology of the sodium hydrosulfide loaded bovine serum albumin nanoparticles (NaHS@BNP) prepared in Example 1 of the present invention was observed using a scanning electron microscope. The results are as follows: Figure 1 As shown in a. It can be seen that the bovine serum albumin nanoparticles loaded with sodium hydrosulfide are regular nanoscale spheres.

[0096] Experimental Example 2: Hydrogen sulfide release of the gas-electrically coupled gelatin and sodium alginate composite hydrogel of the present invention

[0097] 1. Experimental methods

[0098] The gas-electrically coupled gelatin and sodium alginate composite hydrogel (BNP-PEDOT-PSF-AG hydrogel) prepared in Example 1 was immersed in PBS and incubated at 37°C for 25 days. The supernatant was collected by centrifugation every other day (1st, 3rd, 5th, 7th, 9th, 11th, 13th, 15th, 17th, 19th, 21st, 23rd and 25th day), and the released hydrogen sulfide content was detected using a hydrogen sulfide detection kit.

[0099] 2. Experimental results

[0100] like Figure 1As shown in b, the gas-electric coupled gelatin and sodium alginate composite hydrogel of the present invention has a good hydrogen sulfide sustained release effect, and slowly releases hydrogen sulfide gas at 37° C. for more than 20 days.

[0101] Experimental Example 3 Mechanical properties of the gas-electrically coupled gelatin and sodium alginate composite hydrogel of the present invention

[0102] 1. Experimental methods

[0103] After the BNP-PEDOT-PSF-AG hydrogel prepared in Example 1 was freeze-dried, the internal structure of its cross section was observed using an electron microscope.

[0104] The mechanical properties of BNP-PEDOT-PSF-AG, PEDOT-PSF-AG, PSF-AG and AG hydrogels prepared in Example 1 were tested using a universal mechanical tester. The test conditions were a tensile and compression rate of 10 mm / min, the test was stopped after the sample broke, the cycle was compressed to a thickness of 20%, and the compression was repeated 10 times. The length of the tensile test samples was 30 mm, the width was 15 mm, and the thickness was 2 mm. The diameter of the compression test samples was 15 mm and the thickness was 10 mm.

[0105] AG, PSF-AG, PEDOT-PSF-AG and BNP-PEDOT-PSF-AG hydrogels (diameter = 10 mm, thickness = 5 mm, n = 4 per group) were immersed in 1.5 mL of PBS containing type II collagenase (1 μg / mL) at 37°C. The collagenase solution was replaced every 2 days. The specimens were removed at the predetermined time (4th, 8th, 12th, 16th, 20th, 24th day) and freeze-dried. The degradation rate was measured and calculated by residual mass (%) = W1 / W0*100%. Where W1 is the residual mass of the sample and W0 is the initial weight of the hydrogel.

[0106] 2. Experimental results

[0107] Figure 2 The scanning electron microscopy results in a show that the gas-electric coupled gelatin and sodium alginate composite hydrogel (BNP-PEDOT-PSF-AG) prepared in Example 1 has a loose and porous internal structure, indicating that cells are allowed to grow therein.

[0108] like Figure 2 As shown in Figures 2b and 2c, the compressive strength and tensile strength of the BNP-PEDOT-PSF-AG hydrogel of the present invention reached the kilopascal level, and compared with other hydrogels, it can be seen that the introduction of PEDOT-PSF significantly improved the mechanical properties of the gelatin and sodium alginate composite hydrogel.

[0109] like Figure 2As shown in FIG. d, the BNP-PEDOT-PSF-AG hydrogel of the present invention has good cyclic compression performance. Figure 2 As shown in e, the introduction of PEDOT-PSF slowed down the degradation of hydrogel.

[0110] The above results indicate that the mechanical properties of the BNP-PEDOT-PSF-AG hydrogel prepared in the present invention are significantly improved and can withstand the complex mechanical environment of the periodontium.

[0111] Test Example 4: Evaluation of the conductivity of the gas-electrically coupled gelatin and sodium alginate composite hydrogel of the present invention

[0112] 1. Experimental methods

[0113] The conductivity of BNP-PEDOT-PSF-AG (10 mm high × 15 mm in diameter) hydrogel was determined by electrochemical dual probe method. The conductivity (κ, S / m) was calculated by κ=(I / V)(L / A), where A and L are the cross-sectional area and height of the hydrogel, respectively. BNP-PEDOT-PSF-AG hydrogel was prepared by using different amounts of PEDOT-PSF, wherein the content of PEDOT-PSF in the BNP-PEDOT-PSF-AG hydrogel prepared in Table 1 of Example 1 was 2 wt‰, and the BNP-PEDOT-PSF-AG hydrogel with a PEDOT-PSF content of 1 wt‰, 0.5 wt‰, 0.25 wt‰ and 0 wt‰ was prepared according to the amount in Table 1 of Example 1, except that the amount of PEDOT-PSF was replaced by 0.01 g, 0.005 g, 0.0025 g and 0 g. At the same time, according to the above-mentioned conductivity test method, the conductivity of the BNP-PEDOT-PSF-AG hydrogel prepared in Table 1 of Example 1 was measured at different compression amounts (0%, 25%, 50%, 75%).

[0114] At the same time, the conductivity of the hydrogel was tested by light-emitting diodes. The hydrogel and the light-emitting diode were connected into a circuit to observe whether the light-emitting diode emits light under different compression amounts.

[0115] 2. Experimental results

[0116] like Figure 3 As shown in Figs. a and 3c, the BNP-PEDOT-PSF-AG hydrogel of the present invention has good electrical conductivity and can make the LED light bulb inserted therein emit light. Figure 3 As shown in b, the PEDOT-PSF content affects the conductivity of BNP-PEDOT-PSF-AG hydrogel, and the conductivity is optimal when the PEDOT-PSF content is 2wt‰. Figure 3As shown in Figure d, compression of the BNP-PEDOT-PSF-AG hydrogel has little effect on its conductivity, indicating that the conductivity of the hydrogel of the present invention remains stable during the cyclic compression process.

[0117] Experimental Example 5: Evaluation of the biocompatibility of the gas-electric coupled gelatin and sodium alginate composite hydrogel of the present invention

[0118] 1. Experimental methods

[0119] The BNP-PEDOT-PSF-AG, PEDOT-PSF-AG, PSF-AG and AG hydrogels prepared in Example 1 were alternately soaked in anhydrous ethanol and deionized water for one day, and then soaked in PBS for 2 hours before in vitro cell experiments.

[0120] Human periodontal ligament stem cells were seeded on four types of hydrogels. Using α-MEM medium containing 10% fetal bovine serum, they were cultured in a high-glucose and inflammatory in vitro environment (denoted as HL), which was simulated by adding glucose (concentration of 33mM) and lipopolysaccharide (concentration of 100μg / L) to α-MEM medium containing 10% fetal bovine serum. All groups were cultured at 37°C for 3 days, and externally connected to direct currents of 0mV, 300mV, and 600mV (0.5 hours / day, with electrodes inserted into the culture medium). After 3 days of culture, cell morphology was observed by phalloidin staining; and calcium ion dyes were used to analyze the promotion of cellular calcium ion influx by BNP-PEDOT-PSF-AG hydrogel at a voltage of 600mV using flow cytometry. Cell mRNA was extracted with Trizol and sequenced.

[0121] 2. Experimental results

[0122] like Figure 4 As shown in a and 4b, phalloidin staining proves that the BNP-PEDOT-PSF-AG hydrogel prepared in Example 1 has a better effect in promoting cell elongation and arrangement at a voltage of 600mV compared with other hydrogels, indicating that the BNP-PEDOT-PSF-AG hydrogel has better biocompatibility and good cell ductility.

[0123] Further sequencing analysis showed that the expression of genes related to autophagy, cell migration, angiogenesis, and osteogenic differentiation was different ( Figure 4 c), which is closely related to the osteogenic function of the hydrogel. The heat map shows that the expression of autophagy-related genes such as ATG2B and ATG12P1 in BNP-PEDOT-PSF-AG (gas-electric coupling hydrogel group) is upregulated, while the expression of autophagy negative regulation gene SQSTM1 is downregulated ( Figure 4 d), indicating that autophagy was enhanced in the BNP-PEDOT-PSF-AG group. In summary, it is speculated that H2S and bioelectricity synergistically promote osteogenesis by upregulating autophagy ( Figure 4 e).

[0124] Experimental Example 6: Regulatory effect of the gas-electric coupled gelatin and sodium alginate composite hydrogel of the present invention on macrophages

[0125] 1. Experimental methods

[0126] The BNP-PEDOT-PSF-AG, PEDOT-PSF-AG, BNP-PSF-AG, PSF-AG and AG hydrogels prepared in Example 1 were alternately soaked in anhydrous ethanol and deionized water for one day, and then soaked in PBS for 2 hours before in vitro cell experiments.

[0127] Human myeloid leukemia mononuclear cells THP-1 were cultured in 1640 medium containing 10% fetal bovine serum at 37°C and seeded on each hydrogel (2 x 10 5 / mL), and immediately after inoculation, add a final concentration of 100ng mL -1 After 2 days of induction with phorbol (PMA), the culture medium was replaced with a culture medium (HL) simulating a high-glucose and inflammatory environment for 3 days. The culture medium simulating a high-glucose and inflammatory environment was obtained by adding glucose (concentration of 33 mM) and lipopolysaccharide (concentration of 100 μg / L) to 1640 culture medium containing 10% fetal bovine serum.

[0128] After 3 days of culture, RNA was extracted from each group of hydrogels using the Trizol method, and the extracted RNA was reverse transcribed into cDNA using the PrimeScript RT kit. TM 6Flex real-time PCR system and SYBR were used for relative gene quantitative detection (PCR detection). GAPDH was used as an endogenous control to detect the relative gene expression of M1 macrophage-related genes interleukin 1β (IL-1β), tumor necrosis factor α (TNF-α), and inducible nitric oxide synthase (NOS2) in macrophages of each group. The relative gene expression of M2 macrophage-related genes arginase 1 (Arg-1), interleukin 10 (IL-10), and DECTIN in macrophages of each group was detected. Cell mRNA was extracted by Trizol and sequenced for analysis.

[0129] 2. Experimental results

[0130] like Figure 5As shown, the relative expression levels of M1 macrophage-related genes IL-1β, TNF-α and NOS2 in the BNP-PEDOT-PSF-AG hydrogel prepared in Example 1 under a high-glucose inflammatory environment (HL) were the lowest, proving that the expression of inflammation-related factors can be reduced and the polarization of macrophages to the M1 type can be weakened; while the relative expression levels of M2 macrophage-related genes Arg-1, IL-10 and DECTIN were the highest, indicating that BNP-PEDOT-PSF-AG hydrogel can promote the polarization of macrophages to the M2 type.

[0131] Further sequencing GSEA analysis showed that BNP-PEDOT-PSF-AG hydrogels downregulated lipid anabolism and upregulated lipid catabolism ( Figure 5 c and 5d), and the related genes in the gene heat map also showed the same trend ( Figure 5 e), suggesting that lipid metabolism may be the potential mechanism by which the hydrogel regulates macrophage polarization ( Figure 5 f).

[0132] Experimental Example 7: Repairing effect of the gas-electric coupled gelatin and sodium alginate composite hydrogel of the present invention on diabetic periodontitis

[0133] 1. Experimental methods

[0134] 7-week-old SD male rats were purchased from Chengdu Dashuo Biotechnology Co., Ltd. After one week of adaptive feeding, streptozotocin (STZ) was injected intraperitoneally at a dose of 65 mg / kg for 3 consecutive days. One week later, rats showed polydipsia and polyuria. After 4 weeks, their random blood sugar was measured, and those higher than 16.7 mmol / L were considered to be successful diabetes modeling. The silk thread was tied at the neck of the first molar on both sides of the maxillary teeth of diabetic rats, pressed under the gums, and removed after 4 weeks. A vertical incision was made in the mesial part of the first molar to expose the bone loss. The experimental group was placed in Example 1. Prepared BNP-PEDOT-PSF-AG, PEDOT-PSF-AG, BNP-PSF-AG, PSF-AG and AG hydrogels, and the control group was only subjected to sham surgery. Maxillary tissues were collected after 1 week and 4 weeks, and photos of the first molar and surrounding areas were taken (4 weeks), and micro-CT scanning, reconstruction and analysis (4 weeks). The first molar and surrounding bone tissue were fixed, embedded and sliced, and HE staining (4 weeks) and immunofluorescence staining (1 week) were performed.

[0135] 2. Experimental results

[0136] like Figure 6 As shown, the general photo ( Figure 6 a) It was confirmed that the BNP-PEDOT-PSF-AG hydrogel of the present invention promoted the repair of periodontal soft tissue in diabetic rats, reduced gingival recession, eliminated gingival swelling, and fitted the teeth better. micro-CT reconstruction ( Figure 6 b and Figure 6 c) and HE staining ( Figure 6 d) It was confirmed that the BNP-PEDOT-PSF-AG hydrogel of the present invention promoted the repair of periodontal tissues in diabetic rats, the cementum and alveolar bone tissues regenerated well, and orderly arranged periodontal ligament fibers were obtained, indicating that the hydrogel has a better effect of promoting the repair of diabetic periodontitis tissues.

[0137] like Figure 7 As shown by immunofluorescence, more stem cells (CD90) were observed in the periodontal tissue of the BNP-PEDOT-PSF-AG hydrogel group of the present invention, and the best angiogenic (CD31 and α-SMA) and osteogenic properties (OCN and RUNX2) were shown.

[0138] The above results indicate that the BNP-PEDOT-PSF-AG hydrogel prepared in the present invention can significantly promote angiogenesis and bone formation compared with other hydrogels, and has excellent repair effects on diabetic periodontitis.

[0139] In summary, the present invention provides a gas-electrically coupled gelatin and sodium alginate composite hydrogel, which has good biocompatibility and mechanical properties, good stability, can slowly release hydrogen sulfide gas, and has good conductivity, plays an anti-inflammatory and immunomodulatory role, and can also attract stem cells, promote angiogenesis and bone formation, has excellent repair effects on diabetic periodontitis, and has good application prospects.

Claims

1. A gas-electrically coupled gelatin and sodium alginate composite hydrogel, characterized in that: It is prepared from the following raw materials in the following weight ratio: 1-10 parts of gelatin, 1-10 parts of sodium alginate, 0.1-1 parts of polyphenol-modified silk microfibers coupled with 3,4-ethylenedioxythiophene, 0.05-0.5 parts of bovine serum albumin nanoparticles loaded with sodium hydrosulfide, 1-10 parts of polyethylene glycol diglycidyl ether, and 100-200 parts of water.

2. The gas-electrically coupled gelatin and sodium alginate composite hydrogel according to claim 1, characterized in that: It is prepared from the following raw materials in the following weight ratio: 8 parts of gelatin, 2 parts of sodium alginate, 0.2 parts of polyphenol-modified silk microfibers coupled with 3,4-ethylenedioxythiophene, 0.1 parts of bovine serum albumin nanoparticles loaded with sodium hydrosulfide, 6.84 parts of polyethylene glycol diglycidyl ether, and 100 parts of water.

3. The gas-electrically coupled gelatin and sodium alginate composite hydrogel according to claim 1 or 2, characterized in that: The polyphenol-modified 3,4-ethylenedioxythiophene-coupled silk microfibers are prepared from polydopamine-modified silk microfibers, 3,4-ethylenedioxythiophene and ferric chloride hexahydrate as raw materials; The mass volume ratio of the polydopamine-modified silk microfibers and 3,4-ethylenedioxythiophene is 1 g: 1-10 mL; the mass ratio of the polydopamine-modified silk microfibers and ferric chloride hexahydrate is 1:20-30; Preferably, the mass volume ratio of the polydopamine-modified silk microfibers to 3,4-ethylenedioxythiophene is 1 g:4 mL; the mass ratio of the polydopamine-modified silk microfibers to ferric chloride hexahydrate is 1:

20.

4. The gas-electrically coupled gelatin and sodium alginate composite hydrogel according to claim 3, characterized in that: The preparation method of the polyphenol-modified 3,4-ethylenedioxythiophene-coupled silk microfibers comprises the following steps: 1) dispersing polydopamine-modified silk microfibers, 3,4-ethylenedioxythiophene and ferric chloride hexahydrate in a solvent, stirring evenly and then standing; 2) After centrifugation, retain the silk fiber precipitate in the lower layer, wash it with water, and freeze-dry it to obtain the silk fiber precipitate; Preferably, In step 1), the solvent is an ethanol aqueous solution, and the volume ratio of ethanol to water in the ethanol aqueous solution is 3:1; And / or, in step 1), the standing time is 1 to 5 hours.

5. The gas-electrically coupled gelatin and sodium alginate composite hydrogel according to claim 4, characterized in that: The preparation method of the polydopamine-modified silk microfibers comprises the following steps: (a) placing degummed silk into a solution containing dopamine and stirring; (b) after stirring in step (a), half of the solution is replaced with water, and then allowed to stand; (c) adding sodium hydroxide to the solution after standing in step (b), heating for reaction, and then ultrasonic treatment; (d) centrifuging the solution after treatment in step (c), washing the precipitate with water, and freeze-drying to obtain the product.

6. The gas-electrically coupled gelatin and sodium alginate composite hydrogel according to claim 5, characterized in that: In step (a), the mass ratio of the degummed silk fibroin to dopamine is 6:(13-14); And / or, in step (a), the solvent of the dopamine-containing solution is tris-HCl buffer; And / or, in step (a), the stirring time is 10 to 20 hours; And / or, in step (b), the standing time is 10 to 20 hours; And / or, in step (c), the mass ratio of the sodium hydroxide to the degummed silk fibroin in step (a) is (0.7-1):1; And / or, in step (c), the heating reaction temperature is 70-90° C. and the time is 1-5 h; And / or, in step (c), the ultrasonic treatment time is 1 to 5 hours; Preferably, In step (a), the preparation method of degummed silk fibroin comprises the following steps: placing silk in an alkaline solution with a pH of 9 to 10 and boiling it, then cooling it to room temperature, stirring it, and drying it to obtain the degummed silk fibroin.

7. The gas-electrically coupled gelatin and sodium alginate composite hydrogel according to claim 1 or 2, characterized in that: The method for preparing the sodium hydrosulfide-loaded bovine serum albumin nanoparticles comprises the following steps: (A) dissolving bovine serum albumin in water to obtain a bovine serum albumin solution; (B) dissolving sodium hydrosulfide in anhydrous ethanol to obtain a sodium hydrosulfide ethanol solution; (C) adding sodium hydrosulfide ethanol solution to bovine serum albumin solution, and then adding N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride to react; (D) centrifuging after the reaction, collecting the precipitate, and drying the precipitate to obtain; The mass ratio of the bovine serum albumin to sodium hydrosulfide is 1:(0.01-0.05).

8. The gas-electrically coupled gelatin and sodium alginate composite hydrogel according to claim 7, characterized in that: In step (A), the concentration of the bovine serum albumin solution is 1 to 5 wt %; And / or, in step (B), the concentration of the sodium hydrosulfide ethanol solution is 0.1-0.5wt%; And / or, in step (C), the rate of adding the sodium hydrosulfide ethanol solution to the bovine serum albumin solution is 0.1 to 1 mL / min; And / or, in step (C), the mass ratio of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride to bovine serum albumin is (0.01-0.05):1; And / or, in step (C), the reaction temperature is 20-30°C and the reaction time is 10-20h; Preferably, In step (A), the concentration of the bovine serum albumin solution is 2 wt %; And / or, in step (B), the concentration of the sodium hydrosulfide ethanol solution is 0.1wt%; And / or, in step (C), the rate of adding the sodium hydrosulfide ethanol solution into the bovine serum albumin solution is 0.5 mL / min.

9. The method for preparing the gas-electrically coupled gelatin and sodium alginate composite hydrogel according to any one of claims 1 to 8, characterized in that: It includes the following steps: (1) Dissolve gelatin and sodium alginate in water; (2) adding polyphenol-modified 3,4-ethylenedioxythiophene-coupled silk microfibers, sodium hydrosulfide-loaded bovine serum albumin nanoparticles, and polyethylene glycol diglycidyl ether to the solution in step (1) for cross-linking; (3) After crosslinking in step (2), the obtained hydrogel is immersed in a Ca-containing 2+ Further cross-linking in an aqueous solution of ions to obtain; Preferably, In step (2), the cross-linking time is 20 to 30 hours; And / or, in step (3), the cross-linking time is 1 to 5 hours.

10. Use of the gas-electrically coupled gelatin and sodium alginate composite hydrogel according to any one of claims 1 to 8 in the preparation of a drug for treating periodontitis; Preferably, the periodontitis is diabetic periodontitis.

Citation Information

Cited By

  • Hydrogen sulfide response type oxygen release hydrogel and preparation method thereof

    CN121154529A